(untitled) (Książnica Śląska, 2025)
The article discusses the organization of theatre performances and concerts for the SS garrison serving in the Auschwitz concentration camp. The SS men were offered trips to nearby theatres and performances by artists in the extermination camp. The author shows the coexistence of two parallel realities. Furthermore presents information about the shows, comparing them with data on the crimes committed in the concentration camp.